A laser imaging technique for measuring particle distribution at a gas turbine engine inlet - Olshefski, Kristopher T.; Byun, Gwibo; Gillespie, John; Lowe, K. Todd; Ng, Wing F. (Frontiers in Mechanical Engineering, 2025)
The present study demonstrates the novel application of a method for assessing particle spatial distribution at the inlet of a gas turbine engine that is undergoing solid particulate ingestion. Termed the Particle Visualization by Illuminated Scattering (ParVIS) technique, this method requires a laser sheet, camera, and in-situ particle feed rate reference measurement to provide imaging-based measurements of integrated particle mass flow and concentration distribution across the illuminated engine inlet plane. This is accomplished by incorporating an in-situ calibration constant that takes into account both the particle mass flow rate and the integrated pixel intensity across the captured region, which exhibits a proportional relationship. For these tests, a Rolls-Royce M250 turboshaft engine was operated at a ground idle condition (air intake mass flow of 0.744 kg/s), and crushed quartz sand was delivered at a maximum average rate of approximately 1.5 g/min. The results show accurate estimations of the injected particle mass flow, with an average root-mean-square error of 0.06 g/min, or 6%, compared to the monitored mass flow value obtained using a precision scale.